2015
DOI: 10.18632/oncotarget.3586
|View full text |Cite
|
Sign up to set email alerts
|

Low spinophilin expression enhances aggressive biological behavior of breast cancer

Abstract: Spinophilin, a putative tumor suppressor gene, has been shown to be involved in the pathogenesis of certain types of cancer, but its role has never been systematically explored in breast cancer. In this study, we determined for the first time the expression pattern of spinophilin in human breast cancer molecular subtypes (n = 489) and correlated it with survival (n = 921). We stably reduced spinophilin expression in breast cancer cells and measured effects on cellular growth, apoptosis, anchorage-independent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Moreover, we generated stably expressing spinophilin-directed shRNA CRC cell lines and studied the influence of spinophilin expression on cellular phenotypes and molecular interactions. Low spinophilin expression levels are significantly associated with poor prognosis in CRC patients (p = 0.038), a finding that is quite similar to a previously reported study [9] . We confirmed that a reduction of spinophilin levels in p53 wild-type HCT116 and p53-mutated Caco-2 cells were associated with an increase of cellular proliferation and also anchorage-independent growth (p < 0.05).…”
Section: Research Highlightsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, we generated stably expressing spinophilin-directed shRNA CRC cell lines and studied the influence of spinophilin expression on cellular phenotypes and molecular interactions. Low spinophilin expression levels are significantly associated with poor prognosis in CRC patients (p = 0.038), a finding that is quite similar to a previously reported study [9] . We confirmed that a reduction of spinophilin levels in p53 wild-type HCT116 and p53-mutated Caco-2 cells were associated with an increase of cellular proliferation and also anchorage-independent growth (p < 0.05).…”
Section: Research Highlightsupporting
confidence: 90%
“…In addition, growth promoting effects were observed in cell line models and in vivo metastases were promoted. Several potentially differentially expressed genes were discovered by using microarray technology [9] . Taken together, in our studies we evaluated the novel putative tumor suppressor spinophilin in patients with HCC, HNSCC and CRC [4][5][6] .…”
Section: Research Highlightmentioning
confidence: 99%
“…To measure differences in parental adherent growing cells and tumour spheres, which are considered to be enriched of stem/progenitor cancer cells, we established a spheroid growth model as previously described. [ 23 ] In detail, the adherent growing cell lines were dissociated into single cells using trypsin/EDTA and seeded in ultra-low attachment flasks (Corning) using in serum-free McCoy5A medium (SFM). SFM was supplemented with 1xB27 supplement (GIBCO), 20 ng/ml human epidermal growth factor EGF (Peprotech, Rocky Hill, NJ, USA), 20 ng/ml human basic fibroblast growth factor FGF (Peprotech), 20 IU/ml Heparin (Baxter, Vienna, Austria), 4 IU/l insulin actrapid (Novo Nordisk, Vienna, Austria) and 1% antibiotic/antimycotic solution (Sigma-Aldrich, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Breast cancer represents a highly heterogeneous disease in terms of clinical outcomes and biological behavior and thus can be classified with various methods into different subtypes [ 2 ]. In recent years, several novel molecular, cellular, tissue- and blood-based prognostic factors have been identified [ 3 , 4 , 5 ]. In routine clinical practice, however, relying on immunohistochemical analysis of the estrogen receptor (ER), progesterone receptor and her2/neu receptor, breast cancer is subdivided into hormone receptor positive, her2/neu receptor positive, and (lack of all three receptors) triple negative [ 6 ].…”
Section: Breast Cancermentioning
confidence: 99%